Remitting Seronegative Symmetrical Synovitis with Pitting Edema: A Review. (January 2021) - Lakhmalla, Mounika; Dahiya, Dushyant Singh; Kichloo, Asim; Fatima, Tehreem; Edigin, Ehizogie; Wani, Farah
Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) is a rare benign rheumatological condition characterized by sudden-onset symmetrical distal extremity edema. It can present as an isolated disease process or could be associated with other conditions. Rheumatoid factor and anticitrullinated protein antibodies are negative by definition. In current literature, there is paucity of data about the disease process. We performed a literature search using the PubMed database to identify 38 articles that met our inclusion and exclusion criteria. Our literature review focuses on the clinical picture and its diverse associations. Role of various acute phase reactants has also been outlined. There is a generalized consensus among clinicians on using moderate dose steroids for treatment. Other management options for refractory cases have also discussed. Value of several imaging modalities in diagnostic evaluation of this disease entity is touched on. Since RS3PE can be associated with other diseases, specifically cancer, timely diagnosis of this condition is necessary.